PENEGAKAN HUKUM LINGKUNANGAN TERHADAP HAK NELAYAN PADA PROYEK REKLAMASI PELABUHAN NPCT 2 KALIBARU : Peraturan Perlindungan Hak Nelayan dan Lingkungan dalam Proyek Reklamasi di Indonesia - Rahman, Abdul; Nur Azizah Maruf , Siti (Fakultas Hukum Universitas Jambi, 2024)
Indonesia has an extensive coastline, reaching 99,083 kilometers, making it one of the longest in the world and rich in coastal resource potential. However, reclamation activities for infrastructure development often have severe impacts on coastal ecosystems and fishermen's livelihoods. This article discusses legal protection for fishermen and the environment in the context of reclamation. A normative approach is applied, referring to existing laws and regulations. The research and analysis show that reclamation results in marine ecosystem damage, reduced fish catches, changes in shipping routes, and the displacement of fishing communities. Although legal frameworks are in place, their implementation is often weak due to insufficient monitoring and enforcement. Therefore, sustainable law enforcement and active community participation in project planning are essential. This article recommends strengthening legal oversight, providing adequate compensation for affected fishermen, and adopting more environmentally friendly approaches to reclamation. These measures aim to balance infrastructure development with environmental preservation and the well-being of coastal communities, supporting sustainable development in Indonesia.